Fancy nancy sees stars eaudiobook - O'Connor, Jane (I Can Read, Level 1: Fancy Nancy, 2010)
Nancy absolutely adores stars. She loves how they sparkle in the sky, and she can even name the constellations. Nancy can hardly wait for her class visit to the planetarium! Young readers will delight in this newest addition to the Fancy Nancy I Can Read series, sharing in Nancy's anticipation and disappointment when the trip doesn't go as planned. But with her trademark panache, Nancy manages to make even this frustrating situation fun—and, of course, fancy.